Territorialidades acionadas pelo saber-fazer artesanal de mulheres Kaingang da terra indígena Mangueirinha - Piaia, Eliana (2021)
This dissertation addresses the artisanal know-how of Kaingang women from the Mangueirinha Indigenous Land, in the Southwest of Paraná. From the handicrafts, several territorialities are triggered that are expressed by the movements of collection, creation and commercialization of artifacts woven with bamboo and others. These practices and knowledge connect the Indigenous Land and its forest fragments with the cities. The study was built from the decolonial perspective, which allowed the analysis of the violence against indigenous peoples and how they remain in force due to the coloniality of power, knowledge and being. The Kaingang cosmo-ontology, expressed for good living, is a counterpoint to the hegemonic model of development. Their modes of existence are permeated by struggles and claims for rights and recognition. The research was carried out based on ethnography, carried out between the years 2017 and 2021 and which started with my professional contact as a social worker and unfolded with my insertion of master's degree.